2007
DOI: 10.1038/sj.emboj.7601604
|View full text |Cite
|
Sign up to set email alerts
|

Painting of fourth and chromosome-wide regulation of the 4th chromosome in Drosophila melanogaster

Abstract: Drosophila melanogaster exhibits two expression-regulating systems that target whole, specific chromosomes: the dosage compensation system whereby the male-specific lethal complex doubles transcription of genes on the male X-chromosome and the chromosome 4-specific protein Painting of fourth, POF. POF is the first example of an autosome-specific protein and its presence raises the question of the universality of chromosome-specific regulation. Here we show that POF and heterochromatin protein 1 (HP1) are invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
145
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(170 citation statements)
references
References 49 publications
(62 reference statements)
19
145
2
4
Order By: Relevance
“…Interestingly, it has been reported that the protein 'Painting of fourth' (POF) exclusively binds to the fourth chromosome in Drosophila (Larsson et al 2004). The extent of POF binding to fourth chromosome genes is correlated with their transcription levels, and mutational knockouts of POF lead to reduced gene expression on the fourth chromosome (Johansson et al 2007). This suggests that it is involved in chromosome 4-specific gene regulation, perhaps even having a dosage compensation-like role.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that the protein 'Painting of fourth' (POF) exclusively binds to the fourth chromosome in Drosophila (Larsson et al 2004). The extent of POF binding to fourth chromosome genes is correlated with their transcription levels, and mutational knockouts of POF lead to reduced gene expression on the fourth chromosome (Johansson et al 2007). This suggests that it is involved in chromosome 4-specific gene regulation, perhaps even having a dosage compensation-like role.…”
Section: Discussionmentioning
confidence: 99%
“…In the related D. ananassae and D. malerkotliana, POF binds to the fourth chromosome of both sexes but colocalizes with MSL3 on the male X chromosome, suggesting a role in X chromosome compensation in these species (Larsson et al 2004). While POF is nonessential in D. melanogaster with two fourth chromosomes, it is necessary for the survival of flies with a single fourth chromosome, suggesting that POF functions in dosage compensation of the D. melanogaster fourth chromosome ( Johansson et al 2007). POF is a putative RNA-binding protein.…”
Section: à16mentioning
confidence: 99%
“…A deleted cosmid lacking w 1 was used in studies of PEV [w À 4D4.3]. Mutations in msl1, msl2, msl3, and pof have been previously described (Lindsley and Zimm 1992;Johansson et al 2007). Variegating transgene insertions used in this study have been described (Sun et al 2000;Maggert and Golic 2002;Yanet al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The evolution of dosage compensation mechanisms is attributable to evolutionary pressures that act at all levels of expression to compensate for the losses of functional gene copies. Two dosage compensation systems have been studied in Drosophila: the male-specific lethal (MSL) complex, which targets and upregulates the male X chromosome (18,23,56), and the painting of fourth (POF) protein, which stimulates the expression of the fourth chromosome in Drosophila melanogaster but is believed to have originated from a dosage-compensating mechanism (26,(33)(34)(35). The MSL complex and POF coexist; they are on different chromosomes in, e.g., D. melanogaster, but are colocalized on the same chromosome in, e.g., Drosophila ananassae.…”
mentioning
confidence: 99%